Managing without growth : slower by design, not disaster - Victor, Peter A., 1946-; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Ten years after the publication of the first edition of this influential book, the evidence is even stronger that human economies are overwhelming the regenerative capacity of the planet. This book explains why long-term economic growth is infeasible, and why, especially in advanced economies, it is also undesirable. Simulations based on real data show that managing without growth is a better alternative. The book tells how the recent idea of economic growth emerged from the idea of progress, itself only a few hundred years old. Many reasons for questioning growth are given based on an extensive review of the data as well as on conceptual and methodological considerations. The experience of growth in several countries is documented, compared and found wanting. Possibilities for managing without growth in high income economies are simulated with a new, comprehensive systems model with many novel features. Three 50 year scenarios are compared: a base case, an ambitious greenhouse gas reduction scenario, and a sustainable prosperity scenario with broader environmental objectives, reduced income inequality, shorter working hours and the cessation of economic growth. The book closes with a review of policies to make this scenario a reality. This updated book is a valuable resource for a broad academic audience, including students and researchers in economics, environmental studies, environmental science, business studies, and geography, as well as social justice groups and NGOs concerned with the environment, inequality and employment.
Contents: Preface -- 1. The idea of economic growth -- 2. Why manage without growth? -- 3. Systems, information and prices -- 4. Pricing nature -- 5. Limits to growth - sources -- 6. Limits to growth - sinks and services -- 7. Limits to growth - synthesis -- 8. Scale, composition and technology -- 9. Economic growth and happiness -- 10. The disappointments of economic growth -- 11. Managing without growth: exploring possibilities -- 12. Managing without growth: from simulations to reality -- References -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: Economic development -- Social aspects; Economic development -- Environmental aspects; Electronic books